Influence of Facial Morphology on Masticatory Function and Quality of Life in Elders Using Mandibular Overdentures: 3-Year Results - Possebon, Anna Paula da Rosa; Schuster, Alessandra Julie; Marcello-Machado, Raissa Micaella; Martins, Ana Paula Pinto; Pinto, Luciana de Rezende; Chagas-Júnior, Otacílio Luiz; Del Bel Cury, Altair Antoninha; Faot, Fernanda (Frontiers in Nutrition, 2021)
Background: Facial types may interfere in the oral health-related quality of life (OHRQoL) and masticatory performance of implant-retained mandibular overdenture (IMO) wearers. Purpose: Investigate the medium-term changes in the masticatory function (MF) and OHRQoL parameters of IMO users, as a function of facial pattern, anteroposterior skeletal discrepancy, and sex. Methods: Forty IMO users, most of them Caucasian (90%) with average age of 66.31 years were classified according to their facial pattern and antero-posterior discrepancy prior to rehabilitation. MF was evaluated by the multiple sieves method to determine the average particle size (X50), heterogeneity (B) and masticatory efficiency (ME, calculated as the percentage of material retained in the 5.6 and 2.8 mm sieves), using Masticatory performance (MP) and swallowing threshold (ST) tests. OHRQoL was measured by applying the dental impact on daily life (DIDL) questionnaire. The data were analyzed by Wilcoxon-paired tests to analyze changes in MF parameters over time, and mixed-effect multilevel regression models were employed to verify differences between groups. Results: Significant changes were still observed in the 3rd year for the ST test with improvements in B and cycle time for Mesofacial and Dolichofacial individuals, while ME_2.8 deteriorated for Brachyfacial participants. B values of Class I and male individuals improved and brachyfacial individuals still presented worse homogenization (B) than Mesofacial participants in both masticatory tests. Class II and III participants still showed improvements in ME_5.6 and cycle time compared to Class I despite increases in X50. Class II individuals needed less cycles than Class I in the 3rd year. Brachyfacial participants scored lower in the Appearance domain than Mesofacial ones in the 3rd year. Dolichofacial participants and Class III patients scored lower in the Oral Comfort domain than Mesofacial and Class I, respectively. In addition, age influenced the Pain, Oral Comfort and General Performance domains in the 3rd year. Conclusions: Differences in facial morphology continue to influence the MF and OHRQoL outcomes in the 3rd year, and age influenced some OHRQoL domains. Brachyfacial individuals continue to benefit least from rehabilitation with IMO according to masticatory parameters.